Calculation of the Transmission Ratio of 9HP Nine Speed Automatic Transmission - Zhan Changshu; Yan Qiuhan (Jixie chuandong)
Taking a 9 speed automatic transmission （9 AT） of ZF company as study object,it is composed of four planetary gearsets and 6 shift elements. The transmission line of 9 speed automatic transmission is analyzed. The motion equation of each planetary gearset is established. The constraint conditions are built by using the action sequence of shift element. By simultaneous motion equations,the transmission ratio formula of each gear is calculated. The correctness of the formula is verified with the distribution of the transmission ratio of each gearset.